Yusa' Bin Nun In Search of Knowledge and Truth Perspective of Ibn Al Kathir and Al Maraghi's Interpretation of Surah Al-Kahfi ( 60-65 ) - M. Safar Gani; Mohammad Fattah (International Journal of Islamic Educational Research, 2024)
Knowledge and understanding of truth play a pivotal role in shaping the character of youth. The Quran, as the primary source of knowledge in Islam, illustrates this through the story of Yusa' bin Nun, a companion of Prophet Musa, in Surah Al-Kahfi verses 60-65. This research analyzes the role of Yusa' bin Nun in the pursuit of knowledge and truth based on the interpretations of Ibn Al Kathir and Al-Maraghi. Using a qualitative approach and literature review method, the study focuses on two issues: the role of Yusa' bin Nun in seeking knowledge according to Ibn Al Kathir and Al-Maraghi, and the similarities and differences in their opinions. Ibn Al Kathir's interpretation highlights Yusa's loyalty and enthusiasm in seeking knowledge alongside Prophet Musa and Prophet Khidir. Despite facing peculiar actions, Yusa' demonstrates loyalty and conviction, inspiring the younger generation in their scholarly and spiritual journey. Al-Maraghi's interpretation emphasizes the moral role, enthusiasm for learning, and loyalty of Yusa' as symbols of spiritual values. This perspective underscores patience and perseverance in the scholarly journey, revealing that the pursuit of religious knowledge involves profound spiritual experiences. The results of this research provide a deep understanding of the role of youth in seeking knowledge and truth, portraying Yusa' bin Nun as an exemplar of loyalty, enthusiasm for learning, and spiritual experience. This story serves as inspiration for the younger generation, illustrating that the pursuit of knowledge is not merely about acquiring information but also involves profound spiritual experiences.